Análisis crítico de los proyectos de desarrollo microempresarial de mujeres :Caso: Microempresa confección de textiles en el gobierno barrial de Atucucho - Proaño Argüello, Gioconda Patricia (2015)
In 1975 it was carried out in Mexico City the first World Conference of the International Women's Year. The conference’s slogan was: “We are development agents, we are the core of the families' well-being, we contribute with the sexual division in the work, we contribute to the economy and we are diverse”. This conference started the recognition of women as development agents and the necessity that States include policies in order to promote such incorporation. As a product of the conference, it was born the MED (Women in the Development) foundation with the goal of attending women’s basic needs such as: feeding, health, socio-economic equality, water and electric energy supply, etc. focusing on supporting the achievement of welfare for their families and promoting them as economic agents of development. Although women were recognized as development agents in the 70s, it doesn’t mean women have been inserted in the economic market in the same conditions as men. Even in front of the increasing insertion of women in the job market genre inequities persist. They still work in non-professionally qualified areas, mainly in the informal market. In that sense the present work critically analyzes the development projects carried out from the 80s, mainly projects regarding micro entrepreneurships. Throughout this study it is carried out a review of institutions like MED and GED (Genre and Development), as well as a review of many researches which allow checking the required improvements and the foreseen challenges in order to get to a plenty women development.